Risk factors for cancer development in type 2 diabetes. A retrospective case-control study. - Dąbrowski, Mariusz; Szymańska-Garbacz, Elektra; Miszczyszyn, Zofia; Dereziński, Tadeusz; Czupryniak, Leszek (My University, 2016)
Abstract Background. The risk of several types of cancer is increased in type 2 diabetes mellitus. The earliest possible diagnosis of cancer – difficult within regular outpatient diabetes care - is of utmost importance for patients’ survival. The aim of this multicenter, retrospective (years 1998-2015), case-control study was to identify risk factors associated with malignancy in subjects with diabetes treated in a typical outpatient setting. Methods. In the databases of 3 diabetic and 1 primary care clinics 203 patients (115 women) with type 2 diabetes mellitus who developed malignancy while treated for diabetes were identified. The control group consisted of 203 strictly age- and gender matched subjects with type 2 diabetes without cancer. Factors associated with diabetes: disease duration, antidiabetic medications use and metabolic control of diabetes were analyzed. Also other variables: BMI (body mass index), smoking habits, place of residence and comorbidities were included into analysis. Results. The most prevalent malignancies in men and women together were breast cancer (20.7%) and colorectal cancer (16.3%). HbA1c (hemoglobin A1c) level ≥8.5%, obesity and insulin treatment in dose-dependent and time-varying manner demonstrated significant association with increased risk of malignancy, while metformin use was associated with a lower risk of cancer. Diabetes duration, comorbidities, smoking habits, place of residence and aspirin use did not show significant association with risk of malignancy. Conclusions. In the outpatient setting the obese patients with poorly controlled insulin treated type 2 diabetes mellitus should be rigorously assessed towards malignancies, particularly breast cancer in women and colorectal cancer in men.
Keywords: cancer; diabetes; insulin; metformin; obesity